Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw Dengan Sikap Belajar Siswa Terhadap Hasil Belajar Materi Agama Di Smkn 1 Kamal Bangkalan - Aisyah, Siti; Kusmiati; Sunardjo (Penerbit STKIP PGRI Bangkalan, 2024)
This research aims to analyze the effect of implementing the Jigsaw type cooperative learning model on students' learning attitudes and its impact on learning outcomes for religious material at SMKN 1 Kamal Bangkalan. This research is motivated by the importance of creating an active and enjoyable learning atmosphere, as well as increasing student learning motivation. This research used a quasi-experimental design with two groups, namely the experimental group taught using the Jigsaw type cooperative learning model and the control group taught using conventional methods. Data collection was carried out through learning attitude questionnaires and learning outcome tests. The results showed that there were significant differences between the experimental group and the control group. Students in the experimental group showed more positive learning attitudes, such as being more active, responsible, and cooperative. Apart from that, student learning outcomes in the experimental group were also better than those in the control group. Based on the research results, it can be concluded that the Jigsaw type cooperative learning model is effective in improving students' learning attitudes and learning outcomes on religious material. Applying this model can create a more conducive learning atmosphere and motivate students to be more actively involved in the learning process